Feasibility study of liquefied petroleum gas composite cylinder for household users in Malaysia. - Leman, Zulkiflle; Mohammad Borhan; Kheiri, Abouzar (2012)
To increase a tendency among Malaysian to use composite LPG cylinders and make it inevitable to be accepted in the competitive market, this study introduces a new innovative composite cylinder. This cylinder is composed of a slim steel inner liner covered by flax natural fibre inside a 3-pice HDPE casing. Suitability of this cylinder in Malaysia is on the top of this paper’s priorities. This cylinder improves permeability and heat transfer of current composite LPG cylinder with plastic inner liner which are the main issues of these kinds of tanks. Moreover, high cost of raw materials and manufacturing process are considered as the head problem to compete in market .However, new proposed cylinder decreases substantial expenses of manufacturing LPG composite cylinders. Tropical climate of this country sets the stage for using natural fibre in these areas .As a consequence, this method of manufacturing could provide a lot of job opportunity for the local citizens and prevent importing of raw materials.